2000
DOI: 10.1128/jvi.74.4.1892-1899.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction between the Interferon-Induced Protein P56 and the Int6 Protein Encoded by a Locus of Insertion of the Mouse Mammary Tumor Virus

Abstract: For determining cellular functions of the interferon-inducible human cytoplasmic protein P56, we undertook a Saccharomyces cerevisiae two-hybrid screen that identified Int6 as a P56-interacting protein. That the interaction also occurs in human cells was confirmed by coimmunoprecipitation and the observed cytoplasmic displacement of nuclear Int6 upon coexpression of P56. Because Int6 has been claimed to be both a cytoplasmic and a nuclear protein, we investigated the structural basis of this discrepancy. By mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…tertiary structure of the helix and impair the contacts (Guo and Sen, 2000). Previous reports demonstrated that the last three specific TPR motifs in the C-terminal region are required for interaction of IFI56 with the translation initiation factor eIF-3 (Guo and Sen, 2000;Guo et al, 2000a), which is critical for human IFI56 inhibiting cellular protein synthesis, possibly including viral protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…tertiary structure of the helix and impair the contacts (Guo and Sen, 2000). Previous reports demonstrated that the last three specific TPR motifs in the C-terminal region are required for interaction of IFI56 with the translation initiation factor eIF-3 (Guo and Sen, 2000;Guo et al, 2000a), which is critical for human IFI56 inhibiting cellular protein synthesis, possibly including viral protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that the last three specific TPR motifs in the C-terminal region are required for interaction of IFI56 with the translation initiation factor eIF-3 (Guo and Sen, 2000;Guo et al, 2000a), which is critical for human IFI56 inhibiting cellular protein synthesis, possibly including viral protein synthesis. In the present study, all 10 TPR motifs were found in CaIFI58 as compared to human IFI58.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fission yeasts, Int6 deletion mutants accumulate ubiquitinated proteins or misfolded proteins after treatment with canavanine, indicating a proteasome malfunction (9). In addition, it has been shown that Int6 binds the IFN-induced protein p56 during the course of viral infection (13,24). Based on these and other observations, it has been suggested that Int6 may act particularly in cellular stress conditions, which cause protein misfolding during translation or ubiquitination (15).…”
mentioning
confidence: 99%
“…The constitutive photomorphogenesis 9 signalosome is predominantly nuclear (10), eIF3 is cytoplasmic, and the proteasome can be distributed in both cell compartments (11,12). Because Int6 contains a bipartite nuclear localization sequence and a putative NH 2 -terminal nuclear export signal (13), it can shuttle between the nucleus and the cytoplasm and interact with these three complexes (14). All of these observations suggest that Int6 could exert a regulatory activity in both protein translation and degradation and possibly act on specific transcripts (15).…”
mentioning
confidence: 99%